Pengembangan Modul Komikadp untuk Mengurangi Kekerasan dalam Pacaran pada Siswa SMA - Cici Yulia; Khoirunnissa Khoirunnissa; Eka Heriyani (ENLIGHTEN: Jurnal Bimbingan Konseling Islam, 2021)
There are many cases of dating violence in the world and in Indonesia due to lack of of awareness and misinterpreting dating violence as a form of love. The aim of this research is to produce the Komikadp module. The research method used is Research and Development (R&D) method. The research and development model used is 4D Models which was depeloved by Sivasailam Thiagarajan, Dorothy S Semmel, and Melvyn I Semmel. This Model includes four stages, namely, define; design; develop; and disseminate. However, current research and development, used three phases; define, design, and development held at SMA Muhammadiyah DKI Jakarta. Data collection used a checklist as quantitative data and descriptions as qualitative data on the assessment sheet. The Komikadp module that has gone through the three stages received a decent assessment on the aspects of content feasibility, presentation feasibility, language, comic approach in accordance with the guidance and counseling assessment, and graphics based on expert tests and field tests. Thus, the Komikadp Module is very feasible when used by high school studies.